Impact of Inter-Community Conflicts on Wildlife Conservation in Samburu National Reserve and its Environs, Kenya - Ipara, H.; Lemoilea, F.; Waweru, C. (Africa Environmental Review Journal, 2017)
That inter-community conflicts have profound impacts on wildlife conservation cannot be underrated. A study to assess impacts of inter-community conflicts (ICCs) on wildlife conservation was conducted in Samburu National Reserve (SNR) and its environs between December 2014 and May 2015. The study targeted local communities living around the Reserve, SNR personnel and staff from conservation organizations like Save The Elephant (STE) and Ewaso Lions (EL). Data was collected from randomly selected local community respondents using structured questionnaires, discussion and informal consultations, while interviews were held with staff purposively selected from SNR and targeted conservation organizations. Data analysis was done using descriptive statistics and chi-square goodness of fit test. Results were presented using graphs and tables. Results indicated that there was a significant difference between types of inter-community conflicts experienced due to competition over natural resources (χ2=62.923, df=4, p<0.0001). Both the local community and SNR staff noted that although the magnitude of the conflicts experienced was severe, views on causes of the conflict, among them, livestock raiding and competition over resources significantly differed (χ2=27.208, df=4, p<0.0001). Results also showed that opinion on impacts of ICCs on wildlife conservation had a significant difference (χ2=11.426, df=3, p=0.010). Likewise, local community views on measures implemented by SNR management to mitigate the conflicts differed from those of the local community (χ2=5.456, df=3, p=0.125). Views on the effectiveness of measures implemented by both SNR management and the local community also significantly differed ((χ2=3.640, df=2, P=0.162). Opinions of the community on future measures to be taken by the management to mitigate ICCs showed no significant difference (χ2=9.542, df=3, p=0.023). Dialogue, open communication and awareness creation were the most proposed measures to mitigate ICCs in the study area compared to creating a buffer zone or fencing which are viewed as novel measures to conflicts in and around protected areas like SNR. Stakeholder involvement in reconciling the warring communities should be supported with a view to promoting peace and conflict resolution as well as co-existence with wildlife. The local community should be advised to engage in other activities and projects to diversify their livelihoods while supporting SNR management to conserve wildlife.